Information Literacy Skills among the Masters Students of Social Sciences Departments of Mizoram University and Tezpur University A Comparative Study - Verma, Manoj Kumar; Shukla, Ravi (DESIDOC Journal of Library & Information Technology, 2021)
This paper highlights the comparison of information literacy skills among the master’s students of social sciences departments of Mizoram University (MZU) and Tezpur University (TZU). The primary data collected by using survey method and a structured 595 questionnaires were distributed among the respondents in which 522 (87.73 %) of questionnaires were received. The majority of the respondents were female in both the universities in compared to male respondents. Mizoram Universty students have more awareness of using library services in comparison to Tezpur University respondents. It has been also found that there is no significant difference in the information literacy skills of the students of both the Universities. Mizoram University students preferred ‘author-wise’ i.e. (59.32 %) search while Tezpur University students preferred ‘title-wise’ i.e. (39.38 %) search technique for searching the information. It has been also found that a maximum respondents of both universities i.e. (MZU, 55.97 %) and (TZU, 54.75 %) preferred the simple keyword search technique to search the electronic information. The maximum students of both universities were preferred print media for fulfil their needed information. In both of the Universities’ respondents were aware with fair use of information and plagiarism with 79.09 per cent of students at MZU and 84.5 per cent of students at TZU. The maximum 39.16 per cent of students were mostly given the references at MZU while in TZU, a large number 57.53 per cent of students were always giving references when they reproduce other work or ideas. Based on a two-sample t-test, as p<0.05, it was found that no significant difference in the information literacy skills of the students of both the Universities. After testing with Scheffe’s test, it has been shown that the mean of the satisfaction level of respondents was significantly different (P <.05) as the absolute value of the calculated t is smaller than the critical value (0.0737<2.201), which shows that there is no significant difference in the satisfaction level of students of both the Universities towards their library orientation program on the use of library resources and services.